Prinsip-prinsip Syariah dalam Operasional Lembaga Keuangan Syariah - Laila Maulida; Risa Aprilida; Halwa Halimatusadiyah; Fahmi Abdul Mukhsi; Joni Joni; Raihani Fauziyah (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
Islamic financial institutions have emerged as an alternative within the modern financial system, founded on Islamic values and principles. Their main objective is to realize justice, sustainability, balance, and collective welfare in economic activities. This study aims to provide an in-depth explanation of the Sharia principles underlying the operations of Islamic financial institutions, including the prohibition of riba (interest), gharar (uncertainty), and maysir (speculation), as well as the implementation of profit-sharing, justice, transparency, and trustworthiness in all business activities. The research employs a library study method with a qualitative-descriptive approach by analyzing relevant primary and secondary literature sources. The findings indicate that the implementation of Sharia principles not only differentiates Islamic financial institutions from conventional financial systems but also adds significant value through Islamic business ethics, social responsibility, economic sustainability, and protection of customer and community interests. Therefore, a comprehensive understanding of Sharia principles is essential to maintaining the integrity, public trust, and long-term sustainability of Islamic financial institutions in today’s era of global economic development.